Palladium‐Catalyzed Enantioselective Redox‐Relay Heck Alkynylation of Alkenols To Access Propargylic Stereocenters. Issue 23 (3rd May 2017) - Chen, Zhi‐Min; Nervig, Christine S.; DeLuca, Ryan J.; Sigman, Matthew S.
Abstract: An enantioselective redox‐relay Heck alkynylation of di‐ and trisubstituted alkenols to construct propargylic stereocenters is disclosed using a new pyridine oxazoline ligand. This strategy allows direct access to chiral β‐alkynyl carbonyl compounds employing allylic alcohol substrates in contrast to more traditional conjugate addition methods. Abstract : Heck alkynylation : A convenient redox‐relay Heck strategy to synthesize enantiomerically enriched β‐alkynyl carbonyl compounds from allylic alcohols with high functional group tolerance is described. Trisubstituted allylic alcohols are also promising substrates allowing for the formation of propargylic quaternary stereocenters.